Negotiating rites - Hüsken, Ute; Neubert, Frank (Oxford University Press, 2012)
Negotiating karma: penance in the classical Indian law books / Michael Aktor -- Negotiations at death: assessing gifts, mothers, and marriages / Erik de Maaker -- "The clitoris is indeed your sweet": negotiating gender roles in the ritual setting of the Swahili new year's festival / Magnus Echtler -- Ritual negotiations in Lutherland / Barry Stephenson -- Negotiating rites in imperial China: the case of northern Song court ritual debates from 1034 to 1093 / Christian Meyer -- Performing the ancient ones: the body-in-practice as the ground of ritualized negotiation / Nikki Bado -- Negotiating Tantra and Veda in the Parasurama-Kalpa tradition / Annette Wilke -- Jewish same-sex weddings in Canada: rituals of resistance or rituals of conformity? / Shari Rochelle Lash -- The social element of visionary revelation: public rites as a means of negotiating authenticity in Tibetan Buddhist visionary lineages / Amy Holmes-Tagchungdarpa -- Negotiating ritual repair: the prayascitta material in the Baudhāyana Śrauta Sūtra / Kathryn McClymond -- Hook-swinging in south India: negotiating the subaltern space within a colonial society / Ulrike Schröder -- Meaning and enactment in a Buddhist ritual / Patricia Q. Campbell -- Buddhist ordination as initiation ritual and legal procedure / Ute Hüsken, Petra Kieffer-Pülz -- Negotiating the social in the ritual theory of Victor Turner and Roy Rappaport / Grant Potts
Formerly CIP Uk. - Includes bibliographical references and index
Keywords: Aufsatzsammlung; Buddhismus; Hinduismus; Südasien; Ritual; Ritus; Verhandlung